JUAL BELI SEX TOYS DALAM PRESPEKTIF HUKUM PIDANA DI MEDIA ONLINE - Rhafshanjanie Prawira Negara; Frans Simangunsong (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Transactions of pornography on the internet have many stages, starting from offers, agreements, delivery of goods, and payments, it makes many laws and regulations that can be applied. This creates legal uncertainty. The formulation of the problem in this research is how is the form of criminal responsibility for the perpetrators of buying and selling sex toys in online media. This research is a normative legal research. To examine the existing legal problems, this research uses a conceptual approach and legislation. The results of this study indicate that the sale and purchase of pornography (sex toys) through online media can be applied to the ITE Law and Pornography. In terms of accountability, it can be determined from the results of evidence in the trial process what form of pornography is